SS31 alleviates LPS-induced acute lung injury by inhibiting inflammatory responses through the S100A8/NLRP3/GSDMD signaling pathway - Peiyao Luo; Quankuan Gu; Jianpeng Wang; Xianyong Li; Nana Li; Wei Yang; Xianglin Meng; Mingyan Zhao (European Journal of Medical Research)
Abstract Background Acute lung injury/acute respiratory distress syndrome (ALI/ARDS) is an acute, diffuse, inflammatory lung injury caused by various endogenous or exogenous factors. It is currently widely recognized that an excessive inflammatory response resulting from immune imbalance constitutes a crucial pathogenic mechanism in ALI/ARDS. SS31 is a novel mitochondria-targeted antioxidant peptide. This article validates the role of SS31 in lipopolysaccharide (LPS)-induced ALI. Methods The study applied transcriptome sequencing, immunofluorescence, PCR, immunofluorescence and other methods to explore the mechanism of SS31 in LPS induced ALI. Results Transcriptome sequencing results indicate that LPS-induced ALI is closely associated with immune regulatory processes, the Toll-like receptor pathway, and the NF-κB signaling pathway. The role of SS31 in acute lung injury is closely related to biological processes, such as immune regulation and cell death. This study demonstrated that SS31 can inhibit the expression of inflammatory factors IL-6, IL-1β, IL-18, and TNF-α, and reduce the expression of pyroptosis-related proteins NLRP3, and GSDMD-N. Further analysis revealed that S100A8 may be a key gene in the effect of SS31. LPS stimulation leads to increased expression of S100A8, while SS31 decreases its expression. Recombinant protein S100A8 can attenuate the inhibitory effect of SS31 on IL-1β, IL-18, NLRP3, and GSDMD-N. Conclusions The research results indicate that SS31 may inhibit the activation of the NLRP3 inflammasome and suppress inflammatory responses by regulating S100A8, thereby alleviating LPS-induced ALI in mice; this process may be related to pyroptosis.